John Locke and the uncivilized society individualism and resistance in America today - Robinson, Scott, 1981- (Political theory for today., 2021)
"This book analyzes the effect of John Locke's political thought on American political culture today. By analyzing nearly the entirety of Locke's political and philosophical writings, this book shows that Locke's thought has helped to cultivate the incivility seen in recent years in American politics"--